A highly sensitive reversible fluorescent-colorimetric azino bis-Schiff base sensor for rapid detection of Pb2+ in aqueous media. Issue 9 (15th February 2016) - Ghorai, Anupam; Mondal, Jahangir; Saha, Rajat; Bhattacharya, Sumantra; Patra, Goutam K.
Abstract : A reversible fluorescent-colorimetric azino bis -Schiff base receptor for the detection of Pb 2+ in aqueous medium has been developed. Abstract : A reversible fluorescent-colorimetric azino bis-Schiff based receptor for the detection of Pb 2+ in aqueous medium has been developed for the first time. ReceptorL exhibits an excellent selective fluorescent-colorimetric rapid response towards Pb 2+ . The sensitivity of the fluorescence based assay (8 nM) for Pb 2+ is sufficiently low in comparison to that previously reported in the literature. From 1 H NMR data, the Job plot measurement and the ESI-MS spectrum, 2 : 1 stoichiometric complexation betweenL and Pb 2+ has been established. Microstructural features ofL andL + Pb 2+ have been investigated by using SEM images for better understanding the interaction between the chemosensor and Pb 2+ . ReceptorL shows remarkable detection ability in a wide pH range of 4–10 and it has been successfully utilised in the determination of Pb 2+ in aqueous solution of bovine serum albumin protein. The geometry ofL has been optimized both by DFT calculations and single crystal X-ray studies and that of the Pb 2+ complex has been optimized by DFT calculations.